2013
DOI: 10.1088/1367-2630/15/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

Quantum diffusion with disorder, noise and interaction

Abstract: Disorder, noise and interaction play a crucial role in the transport properties of real systems, but they are typically hard to control and study, both theoretically and experimentally, especially in the quantum case. Here, we explore a paradigmatic problem, the diffusion of a wavepacket, by employing ultra-cold atoms in a quasi-periodic lattice with controlled noise and tunable interaction. The presence of quasi-disorder leads to Anderson localization, while both interaction and noise tend to suppress localiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 59 publications
7
60
0
Order By: Relevance
“…With the help of the available experimental apparatus, one aims at simulating in great detail the transition from microscopic to macroscopic scales while accurately adjusting the interaction between the particles, the effect of external (disorder) potentials and/or sources of noise, cf. [14,15] and Section 2.1. Additionally, as the transition towards macroscopic scales involves irreversibility, i. e. an increase of entropy, the question arises under which condition and how a certain system reaches (thermal) equilibrium [16].…”
Section: Part I I N E L a S T I C M U Lt I P L E S C At T E R I N G Omentioning
confidence: 99%
See 3 more Smart Citations
“…With the help of the available experimental apparatus, one aims at simulating in great detail the transition from microscopic to macroscopic scales while accurately adjusting the interaction between the particles, the effect of external (disorder) potentials and/or sources of noise, cf. [14,15] and Section 2.1. Additionally, as the transition towards macroscopic scales involves irreversibility, i. e. an increase of entropy, the question arises under which condition and how a certain system reaches (thermal) equilibrium [16].…”
Section: Part I I N E L a S T I C M U Lt I P L E S C At T E R I N G Omentioning
confidence: 99%
“…In addition to (15), an evolution equation for the non-condensate density ρ nc (r, t) has to be stated in order to solve the coupled equations simultaneously. We will consider such an equation further down.…”
Section: Eq (8) Thus Simplifies Tômentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Anderson himself first noticed the importance of interaction in localization phenomena [8] and launched a theoretical investigation in collaboration with Fleishman [9]. Recently, advances in technology have reinvigorated theoretical [10,11] and experimental [12][13][14][15][16][17][18][19] interest on this subject. For the special case of two interacting particles in a random one-dimensional (1D) potential, Shepelyansky has investigated the interplay of disorder and interaction and concluded that interaction modifies (weakens) localization [20].…”
mentioning
confidence: 99%